The Ritual of Ecolexicon in the Text of Batar in Tetun Fehan Malaka,Timor, East Nusa Tenggara Province: Ecolinguistic View (e-Journal of Linguistics, 2020)
This paper entitled "The Ritual of Ecolexicon in the Text ofBatar in Tetun Fehan Malaka East Nusa Tenggara Province:Ecolinguistic view is a part of the corpus of local wisdom thatneeds to be examined for the sake of sustainability of eternityecology of batar. This research aims to analyze and discover theritual process in text of batar by applying the theory ofecolinguistic focusing on three logical dimensions (ideological,biological, and sociological); that supported the theory oflinguistic and cultural linguistic theory. The approach used in thisresearch is descriptive qualitative with quantitative naturalistic innature.This research applies fieldwork methods. The form ofresearch uses the method of participation observation, interviews,and triangulations. The text of batar is rich of noun, categorical,verb, adjective, and numeral lexicons. The implementation of thefour dimensions of modification gave birth to a totality indissecting the financial ecolexicon in interdependence with theinner rituals, namely ideological dimensions, biologicaldimensions, sociological dimensions and textual dimensions.Keywords: Batar Text, Lexicon, Ritual, Tetun Fehan
Keywords: syntactic typology; valency; nominative-accusative